2022
DOI: 10.1128/mbio.00819-22
|View full text |Cite
|
Sign up to set email alerts
|

The Lectin LecB Induces Patches with Basolateral Characteristics at the Apical Membrane to Promote Pseudomonas aeruginosa Host Cell Invasion

Abstract: An intriguing feature of the bacterium P. aeruginosa is its ability to colonize highly diverse niches. P. aeruginosa can, besides forming biofilms, also enter and proliferate within epithelial host cells. Moreover, research during recent years has shown that P. aeruginosa possesses many different mechanisms to invade host cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The only reported effect of a bacterium on the primary cilium is a study that showed that treatment of cells with P . aeruginosa lectin LecB removed primary cilia in the context of major actin reorganization [ 41 ]. In both these cases, there was no evidence of AurA-HDAC6 pathway involvement, or that primary cilia loss was beneficial to the microbe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only reported effect of a bacterium on the primary cilium is a study that showed that treatment of cells with P . aeruginosa lectin LecB removed primary cilia in the context of major actin reorganization [ 41 ]. In both these cases, there was no evidence of AurA-HDAC6 pathway involvement, or that primary cilia loss was beneficial to the microbe.…”
Section: Discussionmentioning
confidence: 99%
“…The viral protein ORF10 activates the ubiquitin ligase CUL2 ZYG11B , promoting ubiquitination and degradation of IFT46, which is required for primary cilium formation and maintenance. The only reported effect of a bacterium on the primary cilium is a study that showed that treatment of cells with P. aeruginosa lectin LecB removed primary cilia in the context of major actin reorganization [41]. In both these cases, there was no evidence of AurA-H-DAC6 pathway involvement, or that primary cilia loss was beneficial to the microbe.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The P. aeruginosa surface lectin, LecB, was shown to bind β 1-integins causing rapid integrin endocytosis, which loosened cell-substrate adhesion, permitting P. aeruginosa to “crawl” underneath polarized cells ( 53 ). LecB was also shown to bind to fucosylated receptors at the apical plasma membrane of epithelial cells, which results in a Src-PI3K/Akt signaling cascade ultimately leading to the recruitment of caveolin-1 to the apical domain and enhanced invasion efficiency of P. aeruginosa ( 54 ).…”
Section: Bacterial Internalization Mechanisms Into Non-phagocytic Cellsmentioning
confidence: 99%